Concentrations of serum vitamins A, E and C and ?-carotene during pregnancy in cows - Yildiz, H; Kaygusuzoglu, E; Kizil, O (Natl Veterinary Research Inst, 2005)
The concentrations of serum vitamins A, E and C, and P-carotene in 12 cows, between 3-8 years of age, were determined during pregnancy and after delivery. The compounds were assigned spectrophotometrically. It was observed that the levels of vitamins E and C differed during the pregnancy. The level of vitamin A in the 3(rd) month of pregnancy was lower than that in the 7(th) month and the level of beta-carotene in the 4 h month was lower than that in the 6(th) and 7(th) months. It was also noted that the level of vitamin A after delivery was lower than that in months 1, 2, 5, 6, 7, 8 and 9 of pregnancy, but in the 3(rd) and 4(th) months, no statistical difference was observed. Vitamin E level was also lower after parturition than the value noted in the 9(th) month. The level of beta-carotene was lower than the values noted in the 1(st), 6(th), 7(th), 8(th), and 9(th) months as well. The vitamin C level was found to be significantly lower after delivery. It was noted that there was positive correlation between contents of vitamin A and beta-carotene during the whole period of pregnancy. It was also noted a positive correlation (P < 0.01) between vitamin E and beta-carotene in the 6(th) month of pregnancy. It was concluded that the addition of beta-carotene and vitamins A, E and C in sufficient amounts to the rations of the animals before delivery would be beneficial.
Keywords: cows; pregnancy; vitamin A; vitamin E; vitamin C; beta-carotene